Diet and selected stimulants as factors promoting carcinogenesis in oral cancer - Magdalena Kras; Katarzyna Lelek; Dominika Poborowska; Katarzyna Polańska; Weronika Kahan; Weronika Szafrańska; Marta Wojaczek; Piotr Niedbał; Agnieszka Kosińska; Marcin Łata (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose Oral cancer belongs to a heterogeneous group of head and neck cancers. In many cases, it is detected at an advanced stage, which translates into a relatively high mortality rate among patients. For this reason, the identification of risk factors promoting carcinogenesis is of great importance in terms of prevention. The purpose of our study is to demonstrate the relationship between the type of diet consumed and the intake of stimulants and the risk of developing oral cancer. State of knowledge This article is an overview of selected dietary ingredients and stimulants - tobacco, alcohol and betel, presenting their possible effects on the oral area. We have presented both dietary products known for their harmfulness and those with health-promoting effects.  Material and method In our work, we focused on analyzing medical literature available on PubMed and Google Scholar. The sources we have chosen are based on studies conducted in epidemiology, biochemistry and oncology. Summary Dietary habits and ingested stimulants have a direct impact on the development of oral cancer. Depending on the content of various components, the diet may exhibit protective properties or promote carcinogenesis. On the other hand, chronic habitual use of certain substances has been found to be a strong factor in increasing the risk of oral malignancies. Therefore, efforts should be made to raise public awareness of the potential consequences of pro-inflammatory diets and stimulants intake.